Hospital Administration and Nursing Leadership in Disasters: An Exploratory Study Using Concept Mapping - Veenema, Tener Goodwin; Deruggiero, Katherine; Losinski, Sarah; Barnett, Daniel (Nursing administration quarterly, 2017)
Strong leadership is critical in disaster situations when "patient surge" challenges a hospital's capacity to respond and normally acceptable patterns of care are disrupted. Activation of the emergency operations plan triggers an incident command system structure for leadership decision making. Yet, implementation of the emergency operations plan and incident command system protocols is ultimately subject to nursing and hospital leadership at the service- and unit level. The results of these service-/unit-based leadership decisions have the potential to directly impact staff and patient safety, quality of care, and ultimately, patient outcomes. Despite the critical nature of these events, nurse leaders and administrators receive little education regarding leadership and decision making during disaster events. The purpose of this study is to identify essential competencies of nursing and hospital administrators' leadership during disaster events. An integrative mixed-methods design combining qualitative and quantitative approaches to data collection and analysis was used. Five focus groups were conducted with nurse leaders and hospital administrators at a large urban hospital in the Northeastern United States in a collaborative group process to generate relevant leadership competencies. Concept Systems Incorporated was used to sort, prioritize, and analyze the data (http://conceptsystemsinc.com/). The results suggest that participants' institutional knowledge (of existing resources, communications, processes) and prior disaster experience increase leadership competence.